La educación y la mujer, fecundidad educativa - García Ruiz, Isabel (2012)
The present article considers that womanis and educator by nature, dream to bea mother, providing to their children, totheir students, milk and honey, therefore,takes its educational role convinced thatshe is doing in each student a “secondcreation”. The author also considersthe parent education of women is the“pedagogy of love teaching teach”.